Exploring The Strategic Contributions Of Tour Guides To Sustainable Tourism In Bali - I Wayan Agus Selamet; Ni Putu Tiya Paristha; Sang Nyoman Bagus Satya Wira; Atabuy Frit Elisa Yonce; Ni Luh Suparwati (Politeknik Internasional Bali, 2026)
This study explores the strategic contributions of tour guides to sustainable tourism in Bali. The research employed a descriptive qualitative approach using semi-structured interviews with ten certified tour guides in Bali, supported by policy documents and relevant academic literature. Participants were purposively selected based on their professional certification and experience guiding tourists in major destinations such as Ubud, Penglipuran, Tanah Lot, and Nusa Penida. Data were analyzed using thematic content analysis to identify the educational, interpretative, and advocative roles of tour guides in promoting sustainability. The findings reveal that tour guides play a significant role in enhancing tourists’ environmental awareness, encouraging respect for local culture, and advocating responsible tourism practices. Guides were also found to function as cultural mediators who connect tourists with local wisdom and sustainability values through interpretative communication. However, challenges remain, including uneven sustainability competencies, limited institutional support, and economic vulnerability among guides. This study contributes by proposing a strategic framework for strengthening the role of tour guides through sustainability-oriented training, certification improvement, policy integration, and community-based tourism collaboration. The findings provide practical implications for policymakers, tourism stakeholders, and training institutions in advancing sustainable tourism development in Bali.